(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the role of scientific values ​​in the moral and spiritual development of a person and in the development of human society. It is known from history that the economic, political and cultural development of all developed societies is closely related to science and moral values. Of course, science and enlightenment are important in the scientific, technical and economic development of society. However, scientific values ​​have a great influence on the people, the nation, and the moral and spiritual development of a person.